Experimental Study on Methane Hydrate Formation and Transport from Emulsions in a “Gas Lift” Riser in a Flowloop - Pham, Trung-Kien; Cameirao, Ana, Alexandra; Herri, Jean-Michel; Glenat, Philippe (HAL CCSD, 2017)
Session : Flow Assurance: Transportability Strategies - GasHyDyn : Logiciel de simulation de la composition et de la stabilité des hydrates de gaz International audience Production of crude oil with natural gas and water at low temperature and high pressure favours conditions for gas hydrate formation which can cause many troubles, up to blockage of pipelines. This work deals with hydrate kinetics of crystallization and agglomeration together with slurry transport and deposition under flowing conditions. Effects of various parameters are studied including: commercial anti-agglomerant low dosage hydrate inhibitor (AA-LDHI), water volume fraction, and water salinity in a mixture of Kerdane® and water. Experiments were made in the “Archimede” 80 bar flowloop equipped with a FBRM (Focused Beam Reflectance Measurement) and a PVM (Particle Video Microscope) probe and temperature, pressure drop, flow rate and density measurements. The hydrate conversion and volume fraction are calculated from the experimental results. The flow was induced through a “gas lift” system without volumetric pump. The methane is injected at the bottom of the riser at very high flow rate, which enhanced the gas transfer from the bubbles into the liquid phase. The experimental results at high water cut systems revealed a high rate of methane hydrate formation and quick plugging by using our “gas-lift” system (bubble riser). On the contrary, at low water cut systems with the bubble riser, shorter induction time but longer flowing time after gas hydrate formation were observed thanks to salt or AA-LDHI. Some details are given on the mechanism of crystallization, agglomeration and deposition with our “gas lift” system with and without AA-LDHI.